2016
DOI: 10.1128/aem.03191-15
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal Fungal Protein Degradation Ability Predicted by Soil Organic Nitrogen Availability

Abstract: In temperate and boreal forest ecosystems, nitrogen (N) limitation of tree metabolism is alleviated by ectomycorrhizal (ECM) fungi. As forest soils age, the primary source of N in soil switches from inorganic (NH 4 ؉ and NO 3 ؊ ) to organic (mostly proteins). It has been hypothesized that ECM fungi adapt to the most common N source in their environment, which implies that fungi growing in older forests would have greater protein degradation abilities. Moreover, recent results for a model ECM fungal species sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Our results and Keller's contrast with those of Rineau et al (2016). These authors demonstrated growth, protein degradation, and protease activity on BSA in a wide range of Suillus species.…”
Section: Tablesupporting
confidence: 45%
See 1 more Smart Citation
“…Our results and Keller's contrast with those of Rineau et al (2016). These authors demonstrated growth, protein degradation, and protease activity on BSA in a wide range of Suillus species.…”
Section: Tablesupporting
confidence: 45%
“…Similarly, intra-and interspecific diversity yielded complex but generally positive impacts on plant and ECM production with Pinus sylvestris L. seedlings (Hazard, Kruitbos, Davidson, Taylor, & Johnson, 2017). In the most comprehensive study of Suillus isolates to date Rineau et al (2016) demonstrated widespread protease production in vitro with a range of species and species isolates. Most species demonstrated enhanced protease activity when sourced from sites with increased soil organic N availability, however exceptions were observed.…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, some rhizobacterial symbionts of plants also secrete proteases and degrade denatured proteins and scavenge organic nitrogen from soil ( White et al, 2015 ). We might say to strengthen this section that bacterial/fungal chitinase and protease activities are known to participate to the N cycle and are crucial for decomposition of soil organic nitrogen ( Heinonsalo et al, 2015 ; Rineau et al, 2015 ; Knapp and Kovács, 2016 ). Hence, it appears likely that diverse plant-associated fungi and bacteria are important players in the soil nitrogen cycle ( Behie et al, 2013 ).…”
Section: Discussionmentioning
confidence: 96%
“…For instance, N availability plays a key role in CO 2 uptake by plants (Terrer et al, 2016). In the case of ectomycorrhizal fungi, the ability to access N org through secreted proteases has been related to their ecological niche differentiation as part of the natural forest succession (Rineau et al, 2016). For example, in temperate and boreal forest, N is the element limiting tree nutrition (Rees et al, 2001).…”
Section: Discussionmentioning
confidence: 99%